(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article shows the socio-economic significance, scientific and theoretical foundations and advanced foreign experience in training personnel based on the needs of the labor market. An analysis of the personnel training system was also carried out based on the needs of the labor market of the Bukhara region. The state of the labor market and factors affecting the balance of the labor market segment of the Bukhara region are analyzed. Based on the shortcomings identified as a result of the analyzes, ways to ensure the competitiveness of labor resources are shown, promising areas for training, as well as ways to improve training based on the needs of the regional market.